EFEKTIFITAS BIO-KOMPOS DAN BIO-POC TERHADAP SERANGAN HAMA PENGGEREK BATANG (Ostrinia furnacalis) PADA JAGUNG MANIS - Yulensri Yulensri Yulensri (Universitas Muhammadiyah Purwokerto, 2020)
The stem borer (Ostrinia furnacalis Guenee) is one of the main pests of corn. The yield loss due to this pest attack reaches 20-80%. These pests are generally controlled chemically, causing various negative effects from the results of control, therefore environmentally friendly control techniques are needed, such as the use of bio-compost and bio-LOF. Bio-compost is compost combined with a consortium of bacteria Serratia marcecens, Bacillus thuringiensis and Pseudomonas fluorescens. Bio-LOF is a liquid organic fertilizer that is processed using cow feces, cow urine, Glicerida leaves and coconut husk. The research objective is to determine the effectiveness of bio-compost with several concentrations of bio-LOF to control stem borer pests in sweet corn. The research was conducted at experimental land of Payakumbuh Agricultural Polytechnic from January to June 2020. This study used a factorial completely randomized design (4x3) with 3 replications. Factor K, namely K1; Tithonia bio-compost, K2; Hay bio-compost. K3; Manure bio-compost. K4: without bio-compost. Factor D are: D1; Bio-LOF concentration 30%, D2; Bio-LOF 20%. D3: without Bio-LOF. The data obtained were analyzed for variance using a statistical program of 8.0, then continued with the dancun test α 5%. The results showed that the three types of bio-compost combined with bio-LOF could reduce the percentage of O. furnacalis pest attack on the stems and tips of sweet corn cobs. There were 5 treatment combinations with very effective criteria for coefficient of relatively control (CRC), namely. Tithonia bio-compost, Bio-LOF 30%, Hay bio-compost, bio-LOF 30%, chicken feces bio-compost, bio-LOF 30%, Straw bio-compost, Bio-LOF 20%, Without bio-compost, Bio-LOF 30%. The concentration of bio-LOF sprayed on the stems and leaves affects the effectiveness of the control where the 30% bio-LOF concentration had the very effective criteria of control, while the 20% concentration had the effective criteria of control.